The effects of calcium excess,water amount and mixing time on the injectability of calcium phosphate filling materials - Alqap, Asep Sofwan F.; Iis, Sopyan; M. , Husni; N., Athirah (Trans Tech Publications Ltd., Switzerland, 2012)
Variation of calcium excess, water content and mixing time have been taken into the parameters of the injection test of calcium phosphate paste synthesized via low temperature hydrothermal method. The result indicated that all the parameters are very prominent to influence the material injectability possible to be fully injected out the syringe. Strict control of paste synthesizing parameters has successfully overcome poor injectability of the material.